Multigenerational pedigree with STAR syndrome: A novel FAM58A variant and expansion of the phenotype. Issue 5 (21st March 2017) - Boczek, Nicole J.; Kruisselbrink, Teresa; Cousin, Margot A.; Blackburn, Patrick R.; Klee, Eric W.; Gavrilova, Ralitza H.; Lanpher, Brendan C.
Abstract : STAR syndrome is a rare X‐linked dominant disorder characterized by toe Syndactyly, Telecanthus, Anogenital malformations, and Renal malformations, and is caused by loss‐of‐function variants in FAM58A . Our proband presented with the hallmark features of STAR syndrome, as well as some additional less typical features including tethered cord and hearing loss. The proband's mother and maternal half‐sister had similar clinical histories, but had variability in phenotypic severity. Clinical whole exome sequencing revealed a novel pathogenic nonsense variant, c.651G>A (p.Trp217X; NM_152274), in FAM58A in the proband, mother, and maternal half‐sister. This pedigree represents the 11–13th patients described with STAR syndrome and the third instance of familial inheritance. To our knowledge, this is the first occurrence of a nonsense variant in FAM58A described in individuals with STAR syndrome and the phenotype in this pedigree suggests that tethered cord and hearing loss are features of STAR syndrome.